(3efJNH ef cJGH OQQ GdBOGH heMGSf Phj GdCdHGHs - (3eMeO Hf YeQ Hf TGgfTGg CjhH, Gdedc GdefUhQs; (3CHh GdaOGA , UGMH MeGg Gdedc GdeDjO,J (B732 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hcai hGdSdGe Ydi YHGOg dPjf EUWai s
(3BNQgG (B:s
(3Ef GdHNjd hEf CUGH Zfi dJQi Ydjg eNGjd GdabQ s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B282s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(1816 (3c(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs